Leishmania tarentolae and Leishmania infantum in humans, dogs and cats in the Pelagie archipelago, southern Italy. - Roberta Iatta (Public Library of Science (PLoS), 2021)
Visceral leishmaniasis (VL) caused by Leishmania infantum is endemic in the Mediterranean basin with most of the infected human patients remaining asymptomatic. Recently, the saurian-associated Leishmania tarentolae was detected in human blood donors and in sheltered dogs. The circulation of L. infantum and L. tarentolae was investigated in humans, dogs and cats living in the Pelagie islands (Sicily, Italy) by multiple serological and molecular testing. Human serum samples (n = 346) were tested to assess the exposure to L. infantum by immunofluorescence antibody test (IFAT), enzyme-linked immunosorbent assay (ELISA) and Western blot (WB) and to L. tarentolae by IFAT. Meanwhile, sera from dogs (n = 149) and cats (n = 32) were tested for both Leishmania species by IFAT and all blood samples, including those of humans, by specific sets of real time-PCR for L. infantum and L. tarentolae. The agreement between serological tests performed for human samples, and between serological and molecular diagnostic techniques for both human and animal samples were also assessed. Overall, 41 human samples (11.8%, 95% CI: 8.9-15.7) were positive to L. infantum (5.2%, 95% CI: 3.3-8.1), L. tarentolae (5.2%, 95% CI: 3.3-8.1) and to both species (1.4%, 95% CI: 0.6-3.3) by serology and/or molecular tests. A good agreement among the serological tests was determined. Both Leishmania spp. were serologically and/or molecularly detected in 39.6% dogs and 43.7% cats. In addition to L. infantum, also L. tarentolae circulates in human and animal populations, raising relevant public health implications. Further studies should investigate the potential beneficial effects of L. tarentolae in the protection against L. infantum infection.